2016
DOI: 10.2174/1874364101610010044
|View full text |Cite
|
Sign up to set email alerts
|

Detecting IOP Fluctuations in Glaucoma Patients

Abstract: Lowering intraocular pressure (IOP) remains the guiding principle of glaucoma management. Although IOP is the only treatable risk factor, its 24-hour behavior is poorly understood. Current glaucoma management usually relies on single IOP measurements during clinic hours, even though IOP is a dynamic parameter with rhythms dependent on individual patients. It has further been shown that most glaucoma patients have their highest IOP measurements outside clinic hours. The fact that these IOP peaks go largely unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 93 publications
0
9
0
Order By: Relevance
“…The measurement of intraocular pressure (IOP) is an essential examination in daily ophthalmic procedures, also is a fundamental tool in the management and follow-up of glaucoma patients [1]. Many factors, such as central corneal thickness (CCT), corneal astigmatism and biomechanical properties of the cornea can affect the accuracy of IOP measurement [24].…”
Section: Introductionmentioning
confidence: 99%
“…The measurement of intraocular pressure (IOP) is an essential examination in daily ophthalmic procedures, also is a fundamental tool in the management and follow-up of glaucoma patients [1]. Many factors, such as central corneal thickness (CCT), corneal astigmatism and biomechanical properties of the cornea can affect the accuracy of IOP measurement [24].…”
Section: Introductionmentioning
confidence: 99%
“…It has been clearly documented that intraocular pressure (IOP) plays a critical role in the disease process and that elevated IOP is one of the main risk factors for glaucoma progression 2,3 . Yet, in recent years, the advent of continuous IOP telemetry has led to an increased awareness of the importance of IOP fluctuations, and theories have emerged that IOP variations could play as much a role in glaucoma progression as the mean level of IOP [4][5][6] .The SENSIMED Triggerfish (TF) contact lens sensor (CLS) (Sensimed, Lausanne, Switzerland) was the first commercially available device to permit continuous monitoring of IOP-related variations over 24 h. The device consists of a silicone soft contact lens within which a miniaturized telemetric sensor detects subtle fluctuations in ocular volume 7 . While changes in ocular volume were associated with IOP variations, TF CLS do not provide actual IOP measurements, but rather a representation its dynamic variations.…”
mentioning
confidence: 99%
“…Indeed, far from being static, IOP fluctuates widely over the course of 24 hours and through the year, making clinicians' attempts at describing it with a handful of individual values imprecise at best [8][9][10][11][12]. Over the last decades, several studies have suggested that capturing the dynamic nature of IOP through its physiological and environmentally-induced fluctuations could be key to assessing glaucoma stability [13][14][15]. Indeed, such variations, including nocturnal pressure spikes, could contribute directly to retinal ganglion cell damage, regardless of IOP values.…”
Section: Introductionmentioning
confidence: 99%